HUBUNGAN LAMA STUDI DENGAN PERSEPSI MAHASISWA AKAN KEPATUHAN TERHADAP PRINSIP ALARA DI FAKULTAS KEDOKTERAN GIGI UNIVERSITAS BRAWIJAYA - Tubagus Agnizarridlo; Arifandy Irfan Zidan (E-Prodenta Journal of Dentistry, 2023)
Introductions: Radiology plays a vital role in dentistry as a supporting examination. However, dental X-rays pose risks of deterministic and stochastic effects. Therefore, it is necessary to comply with the use of dental X-rays and radiation protection according to the ALARA principle. Perception is the process of receiving messages that are processed into an understanding of the messages received. Meanwhile, compliance is a form of action as the result of the emergence of perceptions with some influencing factors such as the working period. Purpose: This research aims to determine the relationship between the length of study and students' perceptions of compliance with the ALARA principle in the Faculty of Dentistry, Universitas Brawijawa. Methods: This research was conducted through an online survey using social media and the sample was determined using a purposive sampling technique. It used a questionnaire to assess students' perceptions of compliance with the ALARA principle. A total of 196 respondents were selected from three batches adjusted to the target study group. Results: The results showed that the average total score of respondents' perceptions of compliance with the ALARA principle was 73.81 (SD=6.16) and respondents were dominated by a high level of compliance (96.43%). The value of this correlation was calculated and analyzed using the Spearman correlation test. The results of the Spearman correlation test showed that the strength of the positive correlation is weak with a significance score of 0.855 (sig > 0.05). Conclusions: There is no significant relationship between the length of study and students' perceptions of compliance with the ALARA principle in the Faculty of Dentistry, Universitas Brawijawa. Keywords: Length of Study, Perception, Compliance, ALARA